2018
DOI: 10.1021/acssuschemeng.7b04668
|View full text |Cite
|
Sign up to set email alerts
|

A Novel One-Pot Route for Large-Scale Synthesis of Novel Magnetic CNTs/Fe@C Hybrids and Their Applications for Binary Dye Removal

Abstract: Novel magnetic CNTs/Fe@C was prepared via an easy and one-pot method with a high specific surface area (186.3 m2/g) and characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Raman spectra, etc., and it was used for dye removal. Adsorption experiments showed significant differences between single and binary dye systems. The initial adsorption capacities to methylene blue (MB), methyl orange (MO), and neutral red (NR) were 132.58, 16.53, and 98.81 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…The magnetic property of the CF-0 and CF-2 material was investigated by obtaining magnetic hysteresis curves (Figure e). Hysteresis curves of CF-0 and CF-2 showed a saturation magnetization ( M s ) of value of 0.01 and 19.5 emu g –1 , respectively, at 300 K. It is worth noting here that M s for CF-2 is higher than the earlier reports of magnetic adsorbent carbon-γ-Fe 2 O 3 , CNTs/Fe@C, Fe 3 O 4 /V 2 O 5 /rGO composite, nano-Fe 3 O 4 /baker’s yeast composites, and enough to separate the CF-2 from reaction mixture using an external magnetic field (Figure f). The values of saturation magnetization ( M s ), coercivity ( H c ), remanence ( M r ), and ratio between M r and M s compiled in Table S2, suggests that adsorbent CF-2 is in a superparamagnetic state at room temperature, as the ratios of M r / M s are less than 25%. , …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The magnetic property of the CF-0 and CF-2 material was investigated by obtaining magnetic hysteresis curves (Figure e). Hysteresis curves of CF-0 and CF-2 showed a saturation magnetization ( M s ) of value of 0.01 and 19.5 emu g –1 , respectively, at 300 K. It is worth noting here that M s for CF-2 is higher than the earlier reports of magnetic adsorbent carbon-γ-Fe 2 O 3 , CNTs/Fe@C, Fe 3 O 4 /V 2 O 5 /rGO composite, nano-Fe 3 O 4 /baker’s yeast composites, and enough to separate the CF-2 from reaction mixture using an external magnetic field (Figure f). The values of saturation magnetization ( M s ), coercivity ( H c ), remanence ( M r ), and ratio between M r and M s compiled in Table S2, suggests that adsorbent CF-2 is in a superparamagnetic state at room temperature, as the ratios of M r / M s are less than 25%. , …”
Section: Resultsmentioning
confidence: 67%
“…Among different dye removal techniques (which are tabulated in Table S1), the adsorption is widely used as a decontamination technique because of high efficiency and wide applicability. A number of carbon-based adsorbents, e.g., graphene-based composites, carbon nanotubes, and porous carbon, ,, have been explored to remove dyes from the wastewater. The performance of a carbon-layered/nanomaterial could be significantly enhanced due to their high adsorption capacities that originate from the high porosity and surface area. ,,, In search of an economic and effective carbon-based adsorbent for organic pollutants, different biowastes, e.g., tea waste, cotton fabric, and drum sticks, have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…NMs and CMNHs are expected to be stable when solution pH is far away from their pH PZC (pH of point of zero charge); but tend to aggregate at their pH PZC where net surface charge approaches zero. The pH PZC of CNTs, GFNs, CDs, and g-C 3 N 4 is reported at 3–4, , 2.5–3, , 2.0–2.5, and 4–5, , respectively (Figure ). Compared to CNMs, MNPs have higher pH PZC , for example, Al 2 O 3 (pH PZC 8–10), Fe x O y (pH PZC 7–9.5), TiO 2 (pH PZC 6–7.8), and ZnO (pH PZC 7.5–10.2) (Figure ).…”
Section: Energy Water and Environmental Applications Of Cmnhsmentioning
confidence: 98%
“…Reported pH of point of zero charge (pH PZC ) values of CNMs (marked within the red ellipse), CMNHs (marked within the black ellipse), and MNPs (marked within the pink ellipse). Starting from the left x -axis, the first four columns within the red ellipse denote: CNTs (3–4), , GFNs (2.5–3), , CDs (2–2.5), and g-C 3 N 4 (4–5), , respectively. The middle 12 dots/columns within the black ellipse denote: RGO–Fe 3 O 4 (3.7), GO–MnFe 2 O 4 (4.85), RGO–TiO 2 (5.2), g-C 3 N 4 –BiOCl–Cu 2 O–Fe 3 O 4 (5.3), graphene-Co 3 O 4 –Fe 2 O 3 (5.3), CDs–CeZrO 2 (5.8), GO–Co 3 O 4 –Au (5.95), RGO–Fe 3 O 4 (5–6), GO–Al–Fe (6.58), RGO–Fe–Mn (7.47–7.56), CDs-γ–Al 2 O 3 (7.6), and RGO–Zn-Fe (7.8) nanohybrids, respectively.…”
Section: Energy Water and Environmental Applications Of Cmnhsmentioning
confidence: 99%
“…The adsorption isotherm of MO and MB from the prepared hybrids material is shown in Figure 9b. These results suggested that the prepared hybrids had the efficiency to be used as a promising adsorbent for the large-scale applications in binary dye systems, which exhibited a cooperative and competitive adsorption tendency to address the dye pollution effectively [139]. Lee and coworkers fabricated MWCNTs-based polyaniline (PANi)/polyether sulfone (PES) membranes by in situ polymerization of aniline in the presence of MWCNTs for the effective removal of natural organic matter (NOM) in water.…”
Section: Wastewater Treatmentmentioning
confidence: 99%